PENGARUH INTELLECTUAL CAPITAL, FREE CASH FLOW, DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yasri, Salma Zhafirah; Achyani, Fatchan (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to analyze the influence of intellectual capital, free cash flow, and good corporate governance on company value. This type of research includes quantitative research. The population of this study is companies listed on the Indonesia Stock Exchange (IDX). Meanwhile, the sample in this study is manufacturing companies in the consumer goods industry sector for the 2020-2022 period listed on the Indonesia Stock Exchange (IDX). The sampling method in this study is purposive sampling, so that 63 samples were obtained that met the research criteria. The analysis method used is multiple linear regression analysis. The results of this study show that the variables of good corporate governance have an effect on the value of the company, while the variables of intellectual capital and free cash flow have no effect on the value of the company